2005
DOI: 10.1177/000348940511400910
|View full text |Cite
|
Sign up to set email alerts
|

Otosclerosis: Incidence of Positive Findings on High-Resolution Computed Tomography and Their Correlation to Audiological Test Data

Abstract: High-resolution CT scans are a valid tool that can be used to confirm, localize, and determine the size of clinically suspected otosclerotic foci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 15 publications
2
90
1
3
Order By: Relevance
“…Lately, however, radiodiagnostic studies have approached 90 percent or higher sensitivities in diagnosing otosclerosis. The bases for diagnosing otosclerosis in literature arean increase or decrease in width of oval window and sclerotic or hypodense foci on or around footplate [5][6][7], thickened, irregular or hypodense footplate or presence of demineralized areas in temporal bone [4,8] and change in gray scale [9]. We have included the quantitative measurement of the thickness of footplate of stapes as additional decisive diagnostic indicator.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lately, however, radiodiagnostic studies have approached 90 percent or higher sensitivities in diagnosing otosclerosis. The bases for diagnosing otosclerosis in literature arean increase or decrease in width of oval window and sclerotic or hypodense foci on or around footplate [5][6][7], thickened, irregular or hypodense footplate or presence of demineralized areas in temporal bone [4,8] and change in gray scale [9]. We have included the quantitative measurement of the thickness of footplate of stapes as additional decisive diagnostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…On examining images in both axial and coronal views without reconstruction, they found that 26 patients out of a total of 35 patients had a positive finding of a bony excrescence at or adjacent to the oval window. In 2001, Fraysse et al [10] described a sensitivity of 91.3% in finding otosclerosis on CT. Naumann et al [8] found a sensitivity of 85% in localizing an otosclerotic focus in 30 patients suspected to have otosclerosis in 2005, in which study they have commented upon the utility of planar reconstruction and 0.5 mm slices in increasing diagnostic yield. In the present study, multiplanar reconstruction allowed us to study the focus in the best possible plane and made detection easy and accurate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations